2009
DOI: 10.1002/eji.200939536
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of tapasin membrane association and disulfide linkage to ERp57 in MHC class I presentation

Abstract: Summary Tapasin is disulfide linked to ERp57 within the peptide loading complex. In cell-free assays, a soluble variant of the tapasin-ERp57 dimer recruits MHC class I molecules and promotes peptide binding to them while soluble tapasin alone does not. Here we show that within cells, tapasin conjugation with ERp57 is as critical as its integration into the membrane for efficient MHC class I assembly, surface expression, and antigen presentation to CD8-positive T cells. Elimination of both of these properties s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…2B), consistent with a previous finding that soluble tapasin mutants were expressed at higher levels than full-length forms of tapasin (Vigneron et al, 2009). As suggested by Vigneron et al (2009), positively charged residues within the tapasin transmembrane region (e.g. K408 (Petersen et al, 2005)) likely contribute to the destabilization of wild type tapasin and tapasin Δ334-342 as compared to soluble tapasin.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…2B), consistent with a previous finding that soluble tapasin mutants were expressed at higher levels than full-length forms of tapasin (Vigneron et al, 2009). As suggested by Vigneron et al (2009), positively charged residues within the tapasin transmembrane region (e.g. K408 (Petersen et al, 2005)) likely contribute to the destabilization of wild type tapasin and tapasin Δ334-342 as compared to soluble tapasin.…”
Section: Resultssupporting
confidence: 91%
“…Notably, soluble tapasin was highly stable (Fig. 2B), consistent with a previous finding that soluble tapasin mutants were expressed at higher levels than full-length forms of tapasin (Vigneron et al, 2009). As suggested by Vigneron et al (2009), positively charged residues within the tapasin transmembrane region (e.g.…”
Section: Resultssupporting
confidence: 91%
“…14 Wu et al investigated key regulatory molecules involved in prostate cancer (PCA) metastasis in 2 human androgen-independent PCA cell lines, highly metastatic 1E8-H, and lowly metastatic 2B4-L cells by proteomics analyses. They found that calreticulin precursor was upregulated in highly metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other alleles, such as HLA-B27, reach the cell surface but contain a suboptimal peptide repertoire [219]. In a recent study, one of us observed that presentation of two HLA-B*4402-restricted peptides derived from tumor proteins MAGE-A1 and MUM-1 was abolished in the presence of tapasin variants lacking the ability to recruit TAP and ERp57 to the peptide loading complex [220]. These results agreed with previous in vitro studies using recombinant proteins [217,221], and further confirmed that, in the ER environment, the interaction of tapasin with both TAP and ERp57 is required for optimal loading of MHC class I molecules.…”
Section: Tapasinmentioning
confidence: 99%